Superhighway robbery preventing e-commerce crime - Newman, Graeme R. (Willan, 2003)
This book analyzes the expanding crime opportunities created by the Internet and e-commerce, and it explains how concepts of crime prevention developed in other contexts can be effectively applied in this new environment. The authors note that the Internet and associated e-commerce constitute a lawless "wild frontier" where users of the Internet can anonymously exploit and victimize other users without a high risk of being detected, arrested, prosecuted, and punished. For acquisitive criminals who seek to gain money by stealing it from others, e-commerce through the Internet enables them to "hack" their way into bank records and transfer funds for their own enrichment. Computer programs that are readily available for download on the Web can be used to scan the Web for individual computers that are vulnerable to attack. By using the Internet addresses of other users or using another person's or organization's computers or computing environment, criminals can hide their trails and escape detection. After identifying the multiple opportunities for crime in the world of e-commerce, the book describes specific steps that can be taken to prevent e-commerce crime at particular points of vulnerability. The authors explain how two aspects of situational crime prevention can prevent Internet crime. This involves both a targeting of individual vulnerabilities and a broad approach that requires partnerships in producing changes and modifications that can reduce or eliminate criminal opportunities. The authors apply the 16 techniques of situational crime prevention to the points of vulnerability of the e-commerce system. The points of vulnerability are identified and preventive measures are proposed. In discussing the broad approach of institutionalized and systemic efforts to police e-commerce, the book focuses on ways to increase the risks of detection and sanctions for crime without undue intrusions on the freedom and privacy of legitimate Internet and e-commerce users.